Learning Model Role Playing to Skills Speaking Indonesian Students Grade III Elementary School - Ni Komang Martiwi Setiawati; I Ketut Gading; Ni Ketut Desia Tristiantari (Universitas Pendidikan Ganesha, 2026)
This research is motivated by the low speaking skills of third-grade elementary school students, especially in conveying ideas coherently, online to speak in front of friends, and using appropriate vocabulary. This study aims to describe the effect of the Role Playing learning model on improving students' Indonesian speaking skills. The type of research used is quantitative research with a pre-test post-test control group design. The population of this study was all third-grade students in a cluster. The sample used was taken using a random sampling technique, so that two schools were obtained as control and experimental classes. The data collection method and instrument used interview guide sheets and tests. The data analysis technique used quantitative descriptive analysis to see the increase in speaking skill scores before and after treatment. The results showed that the application of role playing was able to increase students' courage, fluency, and ability to convey ideas orally. The implication is that this model can be an alternative effective learning strategy to develop speaking skills, and can be adopted by teachers in creating more active and communicative Indonesian language learning.